2010
DOI: 10.1007/s00404-010-1620-0
|View full text |Cite
|
Sign up to set email alerts
|

Continuous versus interrupted episiotomy repair with monofilament or multifilament absorbed suture materials: a randomised controlled trial

Abstract: The continuous suturing techniques for episiotomy closure, compared to interrupted methods, are associated with less short-term pain, are quicker and also need less suture material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
1
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(46 citation statements)
references
References 11 publications
4
27
1
14
Order By: Relevance
“…5,6 Kokanalı D et al also reported that the continuous suturing techniques for episiotomy closure, compared to interrupted methods, are associated with less short-term pain, are quicker and also need less suture material. 7 In the present study, on 10th day perception of pain during sitting and walking revealed that more subjects had moderate to severe pain in interrupted group which was statistically significant (p value 0.027). Similar observations were made by Kettle C et al who reported in their Meta-analysis that continuous suture techniques compared with interrupted sutures for perineal closure are associated with less pain for up to 10 days' postpartum (risk ratio (RR) 0.76; 95% confidence interval (CI) 0.66 to 0.88, nine trials).…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…5,6 Kokanalı D et al also reported that the continuous suturing techniques for episiotomy closure, compared to interrupted methods, are associated with less short-term pain, are quicker and also need less suture material. 7 In the present study, on 10th day perception of pain during sitting and walking revealed that more subjects had moderate to severe pain in interrupted group which was statistically significant (p value 0.027). Similar observations were made by Kettle C et al who reported in their Meta-analysis that continuous suture techniques compared with interrupted sutures for perineal closure are associated with less pain for up to 10 days' postpartum (risk ratio (RR) 0.76; 95% confidence interval (CI) 0.66 to 0.88, nine trials).…”
Section: Discussionsupporting
confidence: 48%
“…15 But Kokanalı D et al reported that the differences between the pain during sexual intercourse 6 weeks after the delivery were statistically same. 7 Morano S et al reported that no difference was found in superficial dyspareunia at 3 months for the continuous knotless technique versus the interrupted technique group. 10 Kettle C et al in cochrane database systematic reviews reported that there was no evidence of significant differences between groups for dyspareunia at three, or at six to 12 months.…”
Section: Dyspareunia -Reported Up To Three Months After Deliverymentioning
confidence: 97%
See 1 more Smart Citation
“…Concerning perineal pain, the follow-up showed a significant improvement between 3 and 5 days examination and at 6 weeks in the Vicryl TM Rapide group [3]. In a randomized controlled trial in 2010, Kokanalı et al [4] compared four groups of 40 women having delivery with right mediolateral episiotomy. They randomized two groups of continuous suture technique and two groups of interrupted suture technique.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, analgesic consumption has been shown to be significantly lower with Vicryl TM Rapide than with Vicryl TM [2,3]. Concerning the suture method, the continuous suturing technique is associated with less short-term pain [4].…”
Section: Introductionmentioning
confidence: 99%